Clinical feasibility of 2D dynamic sagittal HASTE flexion-extension imaging of the cervical spine for the assessment of spondylolisthesis and cervical cord impingement. Issue 134 (January 2021) - Burke, Christopher J; Samim, Mohammad; Alizai, Hamza; Sanchez, Julien; Kingsbury, Dallas; Babb, James S; Walter, William R
Highlights: Dynamic flexion-extension HASTE is a rapid addition to standard MRI cervical spine protocols. The sequence may useful for assessment of dynamic spondylolisthesis and dynamic cord deformity. HASTE appears reproducible between readers and demonstrates agreement with flex-ex radiographs. Abstract: Purpose: : To assess the utility of a 2D dynamic HASTE sequence in assessment of cervical spine flexion-extension, specifically (1) comparing dynamic spondylolisthesis to radiographs and (2) assessing dynamic contact upon or deformity of the cord. Methods: : Patients with a dynamic flexion-extension sagittal 2D HASTE sequence in addition to routine cervical spine sequences were identified. Static and dynamic listhesis was first determined on flexion-extension radiographs reviewed in consensus. Blinded assessment of the dynamic HASTE sequence was independently performed by 2 radiologists for (1) listhesis and translation during flexion-extension and (2) dynamic spinal cord impingement (cord contact or deformity between neutral, flexion and extension). Results: 32 scans in 32 patients (9 males, 23 females) met inclusion criteria acquired on 1.5 T (n = 15) and 3 T (n = 17) scanners. The mean acquisition time was 51.8 s (range 20–95 seconds). Dynamic translation was seen in 14 patients on flexion-extension radiographs compared to 12 (reader 1) and 13 (reader 2) patients on HASTE, with 90.6 % agreement (K = 0.83; p = 0.789). In all cases dynamic listhesis was ≤3 mm translation with one patient showing dynamic listhesis in the range 4−6 mm. Four cases (13 %) demonstrated deformity of the cord between flexion-extension, not present in the neutral position. For cord impingement there was strong inter-reader agreement (K = 0.93) and the paired sample Wilcoxon signed rank test found no significant difference between the impingement scores of the two readers (p = 0.787). Conclusions: : A sagittal dynamic flexion-extension HASTE sequence provides a rapid addition to standard MRI cervical spine protocols, which may useful for assessment of dynamic spondylolisthesis and cord deformity.